Snapdragons: grandma's glasses - Moon, Nicola; Woody (Oxford University Press Oxford, 2004)
Grandma has lost her glasses. When Grandpa, Harry, Megan, Mum and Scrap help her look, they don't find the glasses, but they do each find something they have lost. At last, Harry finds Grandma's glasses -- on her head!